Error Analysis of Simple Present Tense Using in Students' Descriptive Writing - Lilik Yuliawati (Journal of English Language Learning, 2022)
Simple present tense is one of the most complex tense in English. Because of the different pattern between the students’ mother tongue and English as the target language, students often make errors in producing sentences. The objective of the research is to find out what type of error which mostly appears when students use Simple Present Tense in descriptive writing. This research is a descriptive qualitative research combined with error analysis methodology using Surface Strategy Taxonomy. The research participants were 50 students of Bina Sarana Informatika University majoring Management. The result of the research showed that the most common errors made by students were misformation errors which happened as much as 54%. The second most common errors which appear in students’ descriptive writing were omission errors as much as 24% which number was not much different with addition errors as much as 20%. The least type of error found in students’ descriptive writing was misordering error as much as 2%.